Polyp-Alert: Near real-time feedback during colonoscopy. Issue 3 (July 2015) - Wang, Yi; Tavanapong, Wallapak; Wong, Johnny; Oh, Jung Hwan; de Groen, Piet C.
Highlights We surveyed recent research in polyp detection in screening colonoscopy. We introduced a fast polyp detection algorithm cable of running at 10 frames per second on an off-the-shelf workstation. It correctly detects 97.7% of polyp shots in our data set. We evaluated our technique on 53 video files of procedures performed using Olympus and Fujinon scopes. Real-time polyp detection and feedback potentially help to reduce polyp miss rates to improve quality of care and quality of documentation. The proposed polyp detection algorithm is fast, effective, and potentially useful for improving quality of colonoscopy.